2018
DOI: 10.1080/00071668.2017.1413232
|View full text |Cite
|
Sign up to set email alerts
|

Association ofDGAT2gene polymorphisms with carcass and meat quality traits in domestic pigeons(Columba livia)

Abstract: 1. Diacylglycerol acyltransferase (DGAT) plays an important role in the synthesis of triacylglycerol, but its effects on meat quality and carcass composition in pigeons are unclear. In this study, single-nucleotide polymorphisms (SNPs) in the exons of the DGAT2 gene were identified and analysed by using DNA sequencing methods in 200 domestic pigeons (Columba livia). The associations between DGAT2 polymorphisms and carcass and meat quality traits were also analysed. 2. Sequencing results showed that 5 nucleotid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Yin et al [15] and Li et al [16] reported that a SNP and 13 bp indel in the 3′-UTR of DGAT2 were associated with backfat thickness and lean percentage in pigs. Mao et al [18] found that SNPs in exons 5 and 6 of DGAT2 had an effect on carcass and meat quality traits in domestic pigeons. In goats, variations in exon 3 of DGAT2 were found to be associated with growth traits [35], while variations in exon 4 and intron 5 had an influence on the milk yield and fat percentage [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yin et al [15] and Li et al [16] reported that a SNP and 13 bp indel in the 3′-UTR of DGAT2 were associated with backfat thickness and lean percentage in pigs. Mao et al [18] found that SNPs in exons 5 and 6 of DGAT2 had an effect on carcass and meat quality traits in domestic pigeons. In goats, variations in exon 3 of DGAT2 were found to be associated with growth traits [35], while variations in exon 4 and intron 5 had an influence on the milk yield and fat percentage [17].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of DGAT2 is positively correlated to intramuscular fat (IMF) content in longissimus dorsi muscles of Korean steers [13] and pigs [14]. Variation in DGAT2 has been reported to affect carcass muscle and milk quality traits in various animals, such as fat yield and retail cut weight percentage in commercial feedlot steers [11], backfat thickness and lean percentage in pigs [15,16], milk yield and fat percentage in goats [17], and carcass weight, shear force, and IMF in domestic pigeons [18].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, poultry breeders have focused on the ovaries to study egg production. Moreover, the domestic pigeon is one of the most economically important poultry species in China, as they are a source of meat and eggs, and China is also the largest consumer market for pigeon eggs (Mao et al, 2018). Therefore, it is of great significance to study the regulatory mechanisms of reproduction in ovaries of the pigeon to improve their egg production performance.…”
Section: Introductionmentioning
confidence: 99%
“…Bovine DGAT2 has been mapped to BTA15q25-26 by fluorescence in situ hybridization (FISH) (Winter et al, 2003). Studies have shown that the polymorphisms of DGAT2 gene were associated with economic traits in some domestic animals, such as carcass, meat quality, and fat yield traits in commercial feedlot steers (Li et al, 2009); back-fat thickness in pigs (Yin et al, 2012); carcass weight and shear force in domestic pigeons (Mao et al, 2018); body weight and length in cattle (Zhang et al, 2007;Mao et al, 2008); and milk yield and fat percentage in goats (An et al, 2011).…”
Section: Introductionmentioning
confidence: 99%